The impact of the originate-to-distribute model on banks before and during the financial crisis - Richard J. Rosen (Federal Reserve Bank of Chicago, 2010)
The growth of securitization made it easier for banks to sell home mortgage loans that they originated. I explore how mortgage sales affected banks in the years leading up to the financial crisis that began in 2007 and how their pre-crisis mortgage sales affected banks during the crisis. Loan sales are important because most banks sell mortgages as part of the securitization process, but few actually do the securitization. I find that stock returns increase when banks increase sales of mortgages used for refinancing rather than home purchase, suggesting that some banks scale up lending during refi booms. It is this flexibility that is both a plus and a potential minus of this model, since banks profited by scaling up during refi booms, but borrowers during refi booms were riskier than at other times, possibly adding risk to the financial system. I also find that losses during the financial crisis were related to pre-crisis mortgage sales, with the losses being roughly of the same magnitudes as the gains due to mortgage sales from 2001-2006.
Keywords: 330